Bolivia's green national accounts through a commodity super cycle - Luis Carlos Jemio; Lykke E. Andersen; Agnes Medinaceli (Institute for Advanced Development Studies (INESAD), 2017)
This paper calculates and analyzes key indicators from Bolivia's Green National Accounts during the period 1990 - 2015, which covers an entire Commodity Super Cycle. The first half includes the Great Commodities Depression while the second half of the period is characterized by an unprecedented commodities boom. We show that the contribution of ecosystem goods and services to the Bolivian economy remain relatively stable over the cycle, while the contribution of non-renewable resources increases by a factor of four between the bottom of the cycle (1993) and the top of the cycle (2011). Similarly, the differences between Net Capital Formation and Environmentally-adjusted Net Capital formation is small at the bottom of the Commodity Super Cycle (2.3% of GDP) but much larger at the top of the cycle (7.7% of GDP).
Keywords: Q56; Q01; Q32; Q51; 330; Green Accounting; Natural Resource Rents; Bolivia